2021
DOI: 10.3390/app11167311
|View full text |Cite
|
Sign up to set email alerts
|

Conducting an International, Exploratory Survey to Collect Data on Honey Bee Disease Management and Control

Abstract: The Istituto Zooprofilattico Sperimentale del Lazio e della Toscana (IZSLT) and the International Federation of Beekeepers’ Associations (Apimondia) set up a worldwide survey in 2015–2017 to gather information on beekeepers’ perceptions concerning good beekeeping practices, the main honey bee diseases, and the technical assistance they receive. The on-line dissemination of the survey was facilitated by the “Technologies and Practices for Small Agricultural Producers” platform (TECA) of the Food and Agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…This is also likely reflective of the low percentage of professional beekeepers in both regions (14.4% in the Americas and 16.4% in Europe), considering that migratory beekeeping is a typical activity for professional beekeepers. Our results are consistent with others [28,31] who find that apiculture is a hobby for the overwhelming majority of the beekeepers in the Americas and in Europe and is not likely a primary source of income; future research should examine whether this is the case in other countries and regions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is also likely reflective of the low percentage of professional beekeepers in both regions (14.4% in the Americas and 16.4% in Europe), considering that migratory beekeeping is a typical activity for professional beekeepers. Our results are consistent with others [28,31] who find that apiculture is a hobby for the overwhelming majority of the beekeepers in the Americas and in Europe and is not likely a primary source of income; future research should examine whether this is the case in other countries and regions.…”
Section: Discussionsupporting
confidence: 92%
“…The common use of low-environmental-impact products (the "Soft" acaricides used, 55.1% in the Americas and 53.1% in Europe) was ascribed to oxalic acid, thymol, and formic acid in each of the continents. Similar results were observed by other surveys [21,31]. The beekeepers in the Americas are much more likely to use formic acid compared to their European counterparts (46.9 vs. 27.2%), while Europeans were much more likely to use oxalic acid than those in the Americas (53.9 vs. 39.5%).…”
Section: Discussionsupporting
confidence: 88%
“…This field needs more research, to better understand and shape Varroa control in different countries. Mezher et al (2021) found that the main sources of assistance concerning the control of honey bee diseases were beekeepers' associations and cooperatives, expert beekeepers and veterinarians, while one quarter to one third of beekeepers declared that they did not receive any kind of assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring and analysis should be extended to more European and non-European countries. Further research on the provenance of beekeeping knowledge and decision-making of beekeepers in Varroa control is needed (Mezher et al 2021). Stratification for operation size should be made to understand the different subpopulations of beekeepers (hobbyists, sideliners, professionals).…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
See 1 more Smart Citation